Eight-season epidemiological study of match injuries in women`s international rugby sevens - Fuller, C. W.; Taylor, A. (Journal of Sports Sciences, 2021)
This study aimed to describe anthropometry and incidence, nature and causes of match injuries in women`s international rugby sevens and to compare these with results reported previously for men`s international rugby sevens. The study comprised an 8-season, prospective study of World Rugby`s women`s Sevens World Series. Over the eight seasons, the overall incidence of injury was 105.6 (95% CI: 96.0 to 116.3) injuries/1000 player-match-hours with a mean injury severity of 53.4 (95% CI: 46.9 to 59.9) days-absence. There were no statistically significant trends for backs or forwards in the incidence (backs: p = 0.470; forwards: p = 0.242) or mean severity (backs: p = 0.098; forwards: p = 0.544) of injuries sustained over the 8-season period. Head/face (20.8%), knee (19.7%), ankle (11.3%) and shoulder/clavicle (8.4%) were the most common injury locations while ligament sprain (31.7%), concussion (15.6%), haematoma/bruise (11.5%) and fracture (11.5%) were the most common types of injury sustained. Being-tackled (35.4%), tackling (26.3%), collisions (13.8%) and rucks (8.8%) were the match events responsible for most injuries. The study indicates that injury burden in women`s international rugby sevens (5,640 days-absence/1000 player-match-hours; 95% CI: 5,123 to 6,209) is similar to that reported previously for men`s international rugby sevens (5,263 days-absence/1000 player-match-hours; 95% CI: 5,000 to 5,540).